New Age Manager - A Conceptual Study - Kumar, M. Himesh (Indian Journal of Marketing, 2006)
The desire, the will, the deed and the destiny is the one and only for a young management student i.e., the future manager. Entrepreneurial quality is a rare one with initiative, daring and resourcefulness. It is not necessarily inborn; often many imbibe it. But more entrepreneurs are merely ambitious without the wherewithal to meet the changes of entrepreneurship. Thus, the person turns out to be a successful manager who will be having great expectations-a great risk indeed, but not jumping into the bandwagon of business without any preparation.